Experiencing ChatGPT for Interpersonal Communication Practice: A Case Study of Communication Students Perspective - Tatak, Setiadi; Fitri, Norhabiba; Matty, Senghore (Proceeding of International Joint Conference on UNESA, 2024)
Discussion on the latest technology features has reached the usage of Artificial Intelligence (AI) accessible online through services provided by OpenAI, particularly ChatGPT (Generative Pre-trained Transformer). ChatGPT offers various features capable of answering various commands with relatively fast response times. These features include various topics including interpersonal communication. This research aims to observe and compare the knowledge and answers provided by ChatGPT with the knowledge of the Communication Science students of State University of Surabaya, regarding Interpersonal Communication course through SANRA (a scale for the quality assessment of narrative articles) instrument. The results of this study are expected to provide insights and the latest knowledge about the use of ChatGPT features in Communication Science studies, as well as to give an overview of the opportunities and challenges that will be faced in the students’ academic achievement, especially in higher education.